We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
108
3
avatar

f(x)=x^3-2x, find f(-2)

 

 

help please.

 Nov 30, 2018
 #1
avatar+18333 
+2

Just replace 'x' with -2 and calculate...

(-2)^3 -2(-2) = f(-2)

-8 +4 = -4

 Nov 30, 2018
 #2
avatar
+1

thank you 

Guest Nov 30, 2018
 #3
avatar+647 
0

\(f(-2)=(-2)^3-2(-2)=-8+4=-4\)

 

You are very welcome!

:P

 Dec 1, 2018

24 Online Users

avatar
avatar
avatar